Identity as experience – an interactionist approach - Skott, Jeppe (NOMAD Nordic Studies in Mathematics Education, 2024)
Identity studies tend to draw on participatory frameworks. Some focus on identities on offer in professional development programmes or in general educational discourses; others relate identities to other social worlds and teachers’ biographies. I argue that neither pays sufficient attention to identities as they emerge in school and classroom contexts and that supplementary approaches are needed. In this theoretical essay, I present one such approach that defines professional identities as experiences and combines the definition with an interactionist framework, Patterns-of-participation. I argue that this combination allows interpretations of short- and long-term relationships between identities and school and classroom processes.